Women’s objectification in Charles Bukowski’s post office - Wardani, L Dyah Purwita; Ardiansyah, Mohammad Ridho; Astutiningsih, Irana (Universitas Muhammadiyah Malang, 2023)
This study aimed to evaluate the discourse of women's objectification as portrayed in Charles Bukowski's Post Office novel. Many problems occur in the story, especially problems that revolve around women. They receive adverse treatment from men, both physically and mentally, and are also sexualized. It is critical to consider how literary work contributes to resolving social problems such as women's objectification, male gaze, sexual harassment, and other forms of abuse. The portrayal of women's objectification is traced through Stuart Hall's theory of representation, notably Michel Foucault's discursive approach. The findings of this study demonstrate how the Post Office novel objectifies women as a type of sexual freedom. The Post Office solely shows the female body's external features, focusing specific attention on the sexual organs. These features of women's unfavorable behavior help to objectify them. Bukowski assumed that women are prepared to be mistreated, particularly as sexual objects, in the name of sexual freedom. The Post Office represents male characters, objectifying female characters. Furthermore, some female characters normalize the way they are sexualized, from self-objectification to condescendingly stigmatizing other women. Female characters in the story face sexual objectification, rape, and sexual abuse in the name of sexual freedom.